2021
DOI: 10.1021/acs.biochem.0c00953
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterization of the UDP-Glucose Dehydrogenase Involved in Capsular Polysaccharide Biosynthesis from Campylobacter jejuni

Abstract: Campylobacter jejuni is a pathogenic organism that can cause campylobacteriosis in children and adults. Most commonly, campylobacter infection is brought on by consumption of raw or undercooked poultry, unsanitary drinking water, or pet feces. Surrounding the C. jejuni bacterium is a coat of sugar molecules known as the capsular polysaccharide (CPS). The capsular polysaccharide can be very diverse among the different strains of C. jejuni, and this diversity is considered important for evading the host immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…We have shown that Cj1441 acts as a UDP-glucose 6dehydrogenase to make UDP-glucuronate (4). 14 This molecule is the most likely substrate for the glycosyltransferase that creates the glycosidic bond between D-glucuronate and the C2-hydroxyl from D-ribose at the growing end of the developing polysaccharide chain. The C-terminal domain of Cj1438 catalyzes amide bond formation between the Dglucuronate moiety and (S)-serinol phosphate to make the corresponding glucuronamide phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that Cj1441 acts as a UDP-glucose 6dehydrogenase to make UDP-glucuronate (4). 14 This molecule is the most likely substrate for the glycosyltransferase that creates the glycosidic bond between D-glucuronate and the C2-hydroxyl from D-ribose at the growing end of the developing polysaccharide chain. The C-terminal domain of Cj1438 catalyzes amide bond formation between the Dglucuronate moiety and (S)-serinol phosphate to make the corresponding glucuronamide phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme was crystallized and the protein structure determined to a resolution of 2.1 Å in the presence of UDP-glucose and NAD + . 14 ethanolamine phosphate (8), whereas Cj1437 is a PLPdependent transaminase that catalyzes the stereospecific transamination of dihydroxyacetone phosphate to (S)-serinol phosphate (7). 15 The gene clusters for the biosynthesis of the CPSs made by C. jejuni NCTC 11168 (HS:2) and C. jejuni RM1285 (HS:19) are shown in Figure S1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,20−25 More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose. 26 The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: ■ Introductionmentioning
confidence: 99%
“…jejuni NCTC 11168 is composed of 35 genes, as illustrated in Figure S1 . Previous investigations have functionally characterized the genes necessary for the biosynthesis of the d -glycero- l -gluco-heptose moiety and modification (Cj1152, Cj1423, Cj1424, Cj1425, Cj1427, Cj1428, and Cj1430). In addition, the enzymes Cj1415, Cj1416, Cj1417, and Cj1418 have been shown to be required for the biosynthesis of the phosphoramidate modification, and gene knockout experiments have identified the enzymes (Cj1422 and Cj1421) required for the transfer of the phosphoramidate modifications to specific sugar receptors. , More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose . The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: Introductionmentioning
confidence: 99%